Empowering Rural Women through Kudumbashree Mission: An Analysis of Socio Economic Factors and Structural Constraints - Devika Suresh; R.R. Kushwaha; Supriya; Manish Kumar; Kuldeep Maurya; Sudhanshu Ranjan Yadav; Ashwani Kumar Verma (Archives of Current Research International, 2025)
The study explores the role of Kudumbashree mission in empowerment of rural women by understanding the socio-economic factors and structural constraints faced by the rural women members. The paper identifies the key socio-economic factors and structural constraints that limits the full potential of Kudumbashree mission. The sampling design of this study includes the primary data of 120 respondents collected through personal interview schedules. The study was conducted in the three blocks namely Payyannur, Taliparamba and Irikkur blocks of Kannur district of Kerala particularly and constituted 120 respondents that has been randomly selected from the random four villages in those three blocks of Kannur district respectively. The analytical procedures used here to describe the data particularly includes the methods like average and percentage for the socio-economic factors determination and Friedman test was done through SPSS (Statistical Package for the Social Sciences) was used for determination of the structural constraints. The study findings suggests that while the program has made significant changes in fostering self-reliance among women, a more wider addressing on the structural constraints needed to be done properly.